Modelos y herramientas utilizados en la implementación de sistemas de gestión de calidad (2015)
This paper describes the methodology and importance of the implementation of two models of quality management in the competitiveness of organizations, including: the EFQM self-assessment model and Six Sigma model. The European EFQM model has allowed the company to adopt specialized assessment tools, improving quality management and analysis of results; focused on generating significant benefits in productivity, quality and competitiveness. Described and conceptualized Six Sigma tool oriented elimination or reduction of sources generating defects or errors, ie, contributing to the reduction of process variability.